Graveyard of the Pacific : shipwreck and survival on America's deadliest waterway - Sullivan, Randall (Atlantic Monthly Press, 2023)
"A vivid portrait of the Columbia River Bar that combines maritime history, adventure journalism, and memoir, bringing alive the history--and present--of one of the most notorious stretches of water in the world. Off the coast of Oregon, the Columbia River flows into the Pacific Ocean and forms the Columbia River Bar: a watery collision so turbulent and deadly that it's nicknamed the Graveyard of the Pacific. Two thousand ships have been wrecked on the bar since the first European ship dared to try to cross it in the late eighteenth century. For decades ships continued to make the bar crossing with great peril, first with native guides and later with opportunistic newcomers, as Europeans settled in Washington and Oregon, displacing the natives and transforming the river into the hub of a booming region. Since then, the commercial importance of the Columbia River has only grown, and despite the construction of jetties on either side, the bar remains treacherous, even today a site of shipwrecks and dramatic rescues as well as power struggles between small fishermen, powerful shipowners, local communities in Washington and Oregon, the Coast Guard, and the Columbia River Bar Pilots--a small group of highly skilled navigators who help guide ships through the mouth of the Columbia. When Randall Sullivan and a friend set out to cross the bar in a two-man kayak, they're met with skepticism and concern. But on a clear day in July when the tides and weather seem right, they embark. As they plunge through the waves, Sullivan ponders the generations of sailors that made the crossing before him--including his own abusive father, a sailor himself who also once dared to cross the bar--and reflects on toxic masculinity, fatherhood, and what drives men to extremes. Rich with exhaustive research and propulsive narrative, Graveyard of the Pacific follows historical shipwrecks through the moment-by-moment details that often determined whether sailors would live or die, exposing the ways in which boats, sailors, and navigation have changed over the decades. As he makes his way across the bar, floating above the wrecks and across the same currents that have taken so many lives, Randall Sullivan faces the past, both in his own life and on the Columbia River Bar"--